Combined effect of market orientation and business process agility on the performance of exporting firms in ghana. The moderating roles of institutional voids and market dynamics. - AGYEMANG CHRISTA NYAMEYE (KNUST, 2024)
A thesis submitted to the department of marketing and corporate strategy, Kwame Nkrumah university of science and technology in partial fulfilment of the requirements for the award of master of science degree in marketing